Thrombocytosis in a male patient with acute promyelocytic leukaemia during all-trans retinoic (ATRA) acid treatment - Aldapt, Mohmood B; Kassem, Nancy; Al-Okka, Randa; Ghasoub, Rula; Soliman, Dina; Abdulla, Mohammad A; Mudawi, Deena; Ibrahim, Feryal; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2018)
We present a rather uncommon side effect observed in a 20-year-old man with acute promyelocytic leukemia during treatment with ATRA. He developed a high platelet counts reaching up to 1655×10⁹/L on day 29 of ATRA treatment, and started to recover spontaneously on day 33 of treatment, without any change in ATRA, or adding any cytoreduction therapy. No complications associated with thrombocytosis were observed. IL-6 seems to play an important role in the pathogenesis of the thrombocytosis induced by ATRA. However, it is unclear what are the precipitating factors for this rare phenomenon and whether it is caused by certain predisposing factors that might be related to patient’s, disease pathogenesis or other unknown factors.